The effects of mirror therapy with neuromuscular electrical stimulation on motor and sensory functions in patients with common peroneal nerve injury - Chu, Xiaolei; Liang, Jiajia; Gao, Mingwei; Zhao, Xiaoxuan; Sun, Jiaojiao; Liu, Wenjie; Zhao, Donglin; Xing, Zheng; Li, Qi (Frontiers in Neuroscience, 2025)
BackgroundInjuries to the common peroneal nerve often result in significant sensory and motor function loss, severely affecting patients’ quality of life. Although existing treatments, including medication and surgery, provide some degree of efficacy, their effectiveness is limited by factors such as tolerance and adverse side effects.MethodsThis study aims to evaluate the effects of a 4-week regimen of mirror therapy combined with neuromuscular electrical stimulation on lower limb function, muscle strength, and sensation in patients with common peroneal nerve injuries. The objective is to identify novel therapeutic strategies for lower limb peripheral nerve injuries.30 patients with Common peroneal nerve caused by pelvic fractures were selected from the Rehabilitation Medicine Department of Tianjin Hospital between July 2023 and July 2024. They were randomly divided into two groups: the neuromuscular electrical stimulation group (n = 15) and the mirror therapy with neuromuscular electrical stimulation group (n = 15).ResultsAfter 4 weeks, it was found that mirror therapy with neuromuscular electrical stimulation has a significantly better therapeutic effect on Common peroneal nerve than simple electrical stimulation therapy, particularly in terms of superficial sensation, nerve conduction velocity and ROM.